Diatomite ceramic with crack resistance and high density and preparation method thereof

By using modified diatomaceous earth and other raw materials in ceramics and using specific sintering and glaze firing processes, the problem of diatomaceous earth being prone to deform or cracks during firing is solved, achieving high density and crack resistance and deformation-resistant diatomaceous earth ceramics.

CN119390465AInactive Publication Date: 2025-02-07DEHUAQIAO CRAFTSMAN CERAMIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411544906.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to use diatomaceous earth in ceramics in large quantities because it is prone to deform or cracks during firing and has a low yield.

Method used

By preparing diatomaceous earth ceramics with crack resistance and high density, modifying diatomaceous earth, flux, first binder and reinforcement, combined with three-stage step-by-step temperature-controlled sintering process and glaze firing process, using raw materials such as modified diatomaceous earth, flux, first binder and reinforcement, combined with three-stage step-by-step temperature-controlled sintering process and glaze firing process , a ceramic body and glaze layer with high strength and crack resistance are formed.

Benefits of technology

The high density, crack resistance and deformation resistance of diatomaceous earth ceramics are achieved, the firing rate and yield rate are improved, and the problem of diatomaceous earth easily deforming or cracking during the firing process is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113529550000131
    Figure BDA0005113529550000131
  • Figure BDA0005113529550000141
    Figure BDA0005113529550000141
  • Figure BDA0005113529550000151
    Figure BDA0005113529550000151
Patent Text Reader

Abstract

The invention provides diatomite ceramic with crack resistance and high density and a preparation method thereof. The diatomite ceramic comprises a blank body and a glaze layer, the blank body comprises the following raw materials: diatomite, modified diatomite, kaolin, quartz, feldspar, a fluxing agent, a first binder and a reinforcing agent; the glaze layer is prepared from the following raw materials: modified diatomite, mica powder, talcum powder, feldspar, zinc oxide, a second binder, a stabilizer, a dispersing agent and a wear-resistant additive. The firing time of the green body is 10-12 hours, the green body is fired and molded in a stepped and segmented mode, after glazing, the green body is fired for 5-7 hours, the green body is subjected to glaze firing in a stepped and segmented mode, and the anti-cracking and high-density diatomite ceramic is obtained. According to the invention, the diatomite is used as a main raw material of the green body, the modified diatomite and the compounded additive are utilized to reduce deformation and cracking of the green body in the firing process, increase the strength of the green body and improve the firing rate, and the components of the glaze layer are improved to make the green body and the glaze layer have good compactness, crack resistance and deformation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, in particular to a diatomite ceramic with crack resistance and high density and a preparation method thereof. Background Art

[0002] Diatomite has a unique diatom shell structure and high porosity, but poor plasticity, cannot be sintered alone, and has a low yield rate. The existing raw materials for daily-use ceramics can only account for about 50% of the raw material components when diatomite is used, and cannot be used in large quantities in the mud. In addition, when the diatomite content is high, it is easy to deform or crack during the firing process of the green body, or the glaze layer is easy to crack after the glaze is fired. Therefore, it is urgent to solve the problem of increasing the content of diatomite in ceramics and solving the problem of deformation or cracking during firing. Summary of the invention

[0003] In order to solve the above-mentioned deficiencies of the prior art, the object of the present invention is to provide a diatomite ceramic with crack resistance and high density and a preparation method thereof, so as to overcome the defects in the prior art.

[0004] In order to achieve the above-mentioned object, the present invention provides a diatomite ceramic with crack resistance and high density, wherein the diatomite ceramic comprises a body and a glaze layer; the body comprises the following raw materials in parts by weight: 60-70 parts of diatomite, 15-20 parts of modified diatomite, 5-10 parts of kaolin, 5-10 parts of quartz, 1-5 parts of feldspar, 1-5 parts of flux, 5-8 parts of a first binder, and 1-3 parts of a reinforcing agent; the glaze layer comprises the following raw materials in parts by weight: 40-50 parts of modified diatomite, 5-10 parts of mica powder, 5-10 parts of talc powder, 1-5 parts of feldspar, 1-3 parts of zinc oxide, 1-3 parts of a second binder, 1-3 parts of a stabilizer, 1-3 parts of a dispersant, and 0.5-1 parts of a wear-resistant additive;

[0005] As a further illustration of the diatomite ceramics described in the present invention, preferably, the diatomite ceramics include a body and a glaze layer; the body includes the following raw materials in parts by weight: 65 parts of diatomite, 18 parts of modified diatomite, 8 parts of kaolin, 7 parts of quartz, 3 parts of feldspar, 3 parts of flux, 6 parts of the first binder, and 2 parts of reinforcing agent; the glaze layer includes the following raw materials in parts by weight: 45 parts of modified diatomite, 8 parts of mica powder, 8 parts of talc powder, 3 parts of feldspar, 2 parts of zinc oxide, 2 parts of the second binder, 2 parts of stabilizer, 2 parts of dispersant, and 0.8 parts of wear-resistant additive.

[0006] As a further explanation of the diatomite ceramics described in the present invention, preferably, in the embryo, the flux includes potassium oxide powder and sodium silicate; the first binder includes bentonite, sodium carboxymethyl cellulose and sodium silicate; the reinforcing agent includes inorganic fiber and inorganic powder, the inorganic fiber is selected from at least one of mullite fiber, aluminum silicate fiber and basalt fiber, and the inorganic powder is selected from at least one of aluminum oxide powder, silicon carbide powder and zirconium oxide powder; the average particle size of the flux, the first binder and the reinforcing agent is 10-15 μm. More preferably, the flux is formed by mixing potassium oxide powder and sodium silicate in a mass ratio of 2:1; the first binder is formed by mixing bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2; the reinforcing agent is formed by mixing inorganic fiber and inorganic powder in a mass ratio of 1:1.

[0007] As a further illustration of the diatomite ceramics of the present invention, preferably, in the embryo, the particle sizes of the diatomite, modified diatomite, kaolin, quartz and feldspar are all 300-350 meshes.

[0008] As a further illustration of the diatomite ceramics of the present invention, preferably, in the glaze layer, the second binder includes polyvinyl alcohol and bentonite; the stabilizer includes zirconium silicate and magnesium oxide; the dispersant includes hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide; the wear-resistant additive includes wollastonite and calcium phosphate; the average particle size of the second binder, stabilizer, dispersant and wear-resistant additive is 10-15 μm. More preferably, the second binder is a mixture of polyvinyl alcohol and bentonite in a mass ratio of 1:0.5; the stabilizer is a mixture of zirconium silicate and magnesium oxide in a mass ratio of 1:1; the dispersant is a mixture of hydroxymethyl cellulose, sodium silicate, sodium humate and polyacrylamide in a mass ratio of 1:1:1:2; the wear-resistant additive is a mixture of wollastonite and calcium phosphate in a mass ratio of 1:0.8.

[0009] As a further illustration of the diatomite ceramics of the present invention, preferably, in the glaze layer, the particle sizes of the modified diatomite, mica powder, talc powder and feldspar are all 300-350 meshes.

[0010] As a further illustration of the diatomite ceramics of the present invention, preferably, the modified diatomite is prepared by mixing diatomite, cellulose phosphate and deionized water in a mass ratio of 5:1:40.

[0011] In order to achieve another object of the present invention, the present invention also provides a method for preparing diatomite ceramics, the preparation method comprising the following steps:

[0012] Step 1): diatomaceous earth, cellulose phosphate and deionized water are mixed in a mass ratio of 5:1:40, ultrasonically stirred at a speed of 400-500 r / min for 30-40 minutes, filtered, dried and ground into fine powder to obtain modified diatomaceous earth;

[0013] Step 2): the modified diatomite obtained in step 1) is mixed with diatomite, kaolin, quartz, feldspar, flux, first binder and reinforcing agent according to the raw material ratio of the diatomite ceramic body, and ground with water in a ball mill, sieved and formed into a ceramic body;

[0014] Step 3): After drying the ceramic body obtained in step 2), sintering is performed, at room temperature, the temperature is uniformly increased to 200°C-300°C, fired for 3-3.5 hours, then uniformly increased to 850-950°C, fired for 5-6 hours, then uniformly increased to 1150-1250°C, fired for 2-2.5 hours, and finally naturally cooled to room temperature and fired into shape;

[0015] Step 4): the modified diatomite obtained in step 1) is mixed with mica powder, talc, feldspar, zinc oxide, a second binder, a stabilizer, a dispersant, and a wear-resistant additive according to the raw material ratio of the diatomite ceramic glaze layer, and the mixture is ground with water in a ball mill and sieved to obtain a ceramic glaze;

[0016] Step 5): applying the ceramic glaze obtained in step 4) to the ceramic body formed by firing in step 3) to form a glaze layer, and after the glaze layer on the ceramic body is dried, glaze firing is performed. At room temperature, the temperature is increased to 400°C-500°C in 2-2.5h, then increased to 850-950°C in 2.5-3h, and kept warm for 30min, and then increased to 1150-1250°C in 0.5-1.5h, and kept warm for 30min, and finally naturally cooled to room temperature to obtain diatomite ceramics with crack resistance and high density.

[0017] As a further illustration of the preparation method of the present invention, preferably, in step 2), the moisture content of the ceramic body is 20-25%; and in step 4), the moisture content of the ceramic glaze is 45-55%.

[0018] As a further illustration of the preparation method of the present invention, preferably, the glaze layer thickness of the diatomite ceramic is 0.6-0.8 mm.

[0019] The beneficial effects of the present invention are as follows:

[0020] The ceramic body of the present invention uses diatomite as the main raw material, utilizes cellulose phosphate to react with the hydroxyl group on the surface of diatomite to obtain modified diatomite, enhances the adsorption capacity of kaolin, quartz and feldspar, reduces the deformation and cracking of the body during the firing process, increases the strength of the body, and improves the firing rate; by adding a fluxing agent formed by a mixture of potassium oxide powder and sodium silicate, the firing temperature of the body can be reduced, the melting of the raw materials can be promoted, and the density of the body can be improved; by adding a first binder formed by a mixture of bentonite, sodium carboxymethyl cellulose and sodium silicate, the diatomite, modified diatomite, kaolin, quartz and the like are increased. The bonding compatibility between the inorganic fiber and the feldspar improves the strength of the green body, and during the green body firing process, it helps to evenly discharge the moisture inside the green body, adjust the drying shrinkage and firing shrinkage of the green body, and improve the compactness and crack resistance of the green body; by adding a reinforcing agent mixed with inorganic fibers (at least one of mullite fibers, aluminum silicate fibers, and basalt fibers) and inorganic powders (at least one of alumina powders, silicon carbide powders, and zirconium oxide powders), the inorganic fibers improve the crack resistance of the green body during the firing process, increase the toughness of the green body, and the inorganic powders help to improve the density of the ceramic during the sintering process. Therefore, the ceramic green body of the present invention not only has high strength, but also has good compactness, crack resistance, and deformation resistance.

[0021] The glaze layer of the present invention uses modified diatomaceous earth, mica powder, talc powder, feldspar and zinc oxide as basic raw materials. The mica powder can form layers of microstructures in the ceramic. During the firing process, these layered structures can effectively prevent the ceramic from cracking during the firing process, thereby enhancing the strength and toughness of the glaze layer; the stone powder helps to control the shrinkage of the glaze surface during the high-temperature firing process to avoid the glaze surface from cracking due to excessive shrinkage; by adding a second binder formed by mixing polyvinyl alcohol and bentonite, the adhesion and hardness of the glaze can be improved, and the smoothness, wear resistance and crack resistance of the glaze surface can be enhanced; by adding a stabilizer formed by mixing zirconium silicate and magnesium oxide, magnesium oxide can enhance the thermal stability of the glaze, and synergistically act with zirconium silicate to reduce the cracking and deformation of the glaze layer caused by temperature changes. , improve the crack resistance, deformation resistance and wear resistance of ceramic products; by adding a dispersant mixed with hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide, hydroxymethyl cellulose can prevent problems such as cracking and deformation caused by water loss during the molding process, sodium hexametaphosphate can improve the adhesion and hardness of the glaze, and synergistically improve the gloss and wear resistance of the glaze with sodium silicate, polyacrylamide can reduce cracks and defects during the sintering process of the product, thereby increasing the crack resistance and deformation resistance of the ceramic as a whole; by adding a wear-resistant additive mixed with wollastonite and calcium phosphate, the hardness and wear resistance of the glaze can be improved, and calcium phosphate increases the hardness and wear resistance of the glaze, and reduces the defects of bubbles, bursts and cracks on the glaze, thereby improving the quality of the glaze. Therefore, the ceramic glaze layer of the present invention also has good density, crack resistance and deformation resistance.

[0022] In addition, the bentonite, zirconium silicate and magnesium oxide, sodium hexametaphosphate and sodium silicate, wollastonite and calcium phosphate added to the glaze layer of the present invention can enhance the wear resistance of the glaze surface; the bentonite also acts as a suspending agent to prevent the glaze from agglomerating; the dispersants hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide increase the fluidity of the glaze, thereby making the glaze layer more uniform and delicate, and increasing the uniformity of the ceramic glaze layer after glaze firing; the synergistic effect of polyvinyl alcohol, bentonite and sodium silicate makes the glaze surface brighter and more uniform, and together with wollastonite, improves the glossiness of the glaze layer; thereby enhancing the light transmittance of the glaze surface, and improving the aesthetics and durability of the ceramic product.

[0023] The preparation method of the present invention can obtain diatomite ceramics with high strength, high density, crack resistance and deformation resistance by controlling the temperature and time of ceramic body biscuit firing in three stages and controlling the temperature and time of glaze firing in three stages after the ceramic body is glazed. DETAILED DESCRIPTION

[0024] In order to further understand the structure, features and other purposes of the present invention, the following detailed description is given in conjunction with the attached preferred embodiments. This embodiment is only used to illustrate the technical solution of the present invention and is not intended to limit the present invention.

[0025] Example 1: A method for preparing diatomite ceramics

[0026] Preparation of modified diatomaceous earth: diatomaceous earth, cellulose phosphate and deionized water were mixed in a mass ratio of 5:1:40, ultrasonically stirred at a speed of 400 r / min for 30 minutes, filtered, dried and ground into fine powder to obtain modified diatomaceous earth.

[0027] Preparation of ceramic green body: firstly, 15 parts of the prepared modified diatoms are mixed with 60 parts of diatomite, 5 parts of kaolin, 5 parts of quartz, 1 part of feldspar, 1 part of flux (mixed by potassium oxide powder and sodium silicate in a mass ratio of 2:1), 5 parts of the first binder (including bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2), and 1 part of reinforcing agent (including mullite fiber and alumina powder in a mass ratio of 1:1), and then water is added to grind in a ball mill, sieve, and molded into a ceramic green body with a moisture content of 20%. The particle size of diatomite, modified diatomite, kaolin, quartz and feldspar is preferably 300 mesh. Then, after the ceramic body is dried, it is sintered. At room temperature, the temperature is uniformly increased to 200°C, fired for 3 hours, then uniformly increased to 850°C, fired for 5 hours, then uniformly increased to 1150°C, fired for 2 hours, and finally naturally cooled to room temperature to obtain a fired ceramic body. Preferably, when the ceramic body is dried and the difference in moisture content inside and outside the ceramic body is maintained at 1%, the ceramic body is sintered.

[0028] Preparation of ceramic glaze: 40 parts of the prepared modified diatomite are mixed with 5 parts of mica powder, 5 parts of talc powder, 1 part of feldspar, 1 part of zinc oxide, 1 part of a second binder (including polyvinyl alcohol and bentonite in a mass ratio of 1:0.5), 1 part of a stabilizer (including zirconium silicate and magnesium oxide in a mass ratio of 1:1), 1 part of a dispersant (including hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide in a mass ratio of 1:1:1:2), and 0.5 parts of a wear-resistant additive (including wollastonite and calcium phosphate in a mass ratio of 1:0.8), and water is added to the ball mill for grinding and sieving to obtain a ceramic glaze with a water content of 45%. The particle size of the modified diatomite, mica powder, talc powder and feldspar is preferably 300 mesh.

[0029] Preparation of diatomite ceramics: first apply the obtained ceramic glaze to the fired ceramic body to form a glaze layer. Then, after the glaze layer on the ceramic body is dried, glaze firing is performed. At room temperature, the temperature is raised to 400°C in 2 hours, then raised to 850°C in 2.5 hours, kept warm for 30 minutes, then raised to 1150°C in 0.5 hours, kept warm for 30 minutes, and finally cooled naturally to room temperature to obtain a diatomite ceramic with a glaze layer thickness of 0.6 mm.

[0030] Example 2: A method for preparing diatomite ceramics

[0031] Preparation of modified diatomaceous earth: diatomaceous earth, cellulose phosphate and deionized water were mixed in a mass ratio of 5:1:40, ultrasonically stirred at a speed of 450 r / min for 35 minutes, filtered, dried and ground into fine powder to obtain modified diatomaceous earth.

[0032] Preparation of ceramic green body: firstly, 18 parts of the prepared modified diatoms are mixed with 65 parts of diatomite, 8 parts of kaolin, 7 parts of quartz, 3 parts of feldspar, 3 parts of flux (mixed by potassium oxide powder and sodium silicate in a mass ratio of 2:1), 6 parts of the first binder (including bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2), and 2 parts of reinforcing agent (including mullite fiber and alumina powder in a mass ratio of 1:1), and then water is added to grind in a ball mill, sieve, and molded into a ceramic green body with a moisture content of 22%. The particle size of diatomite, modified diatomite, kaolin, quartz and feldspar is preferably 320 mesh. Then, after the ceramic body is dried, it is sintered. At room temperature, the temperature is uniformly increased to 250°C, fired for 3.2 hours, then uniformly increased to 900°C, fired for 5.5 hours, then uniformly increased to 1200°C, fired for 2.3 hours, and finally naturally cooled to room temperature to obtain a fired ceramic body. Preferably, when the ceramic body is dried and the difference in moisture content inside and outside the ceramic body is maintained at 1%, the ceramic body is sintered.

[0033] Preparation of ceramic glaze: 45 parts of the prepared modified diatomite are mixed with 8 parts of mica powder, 8 parts of talc powder, 3 parts of feldspar, 2 parts of zinc oxide, 2 parts of a second binder (including polyvinyl alcohol and bentonite in a mass ratio of 1:0.5), 2 parts of a stabilizer (including zirconium silicate and magnesium oxide in a mass ratio of 1:1), 2 parts of a dispersant (including hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide in a mass ratio of 1:1:1:2), and 0.8 parts of a wear-resistant additive (including wollastonite and calcium phosphate in a mass ratio of 1:0.8), and water is added to the ball mill for grinding and sieving to obtain a ceramic glaze with a water content of 48%. The particle size of the modified diatomite, mica powder, talc powder and feldspar is preferably 320 mesh.

[0034] Preparation of diatomite ceramics: first apply the obtained ceramic glaze to the fired ceramic body to form a glaze layer. Then, after the glaze layer on the ceramic body is dried, glaze firing is performed. At room temperature, the temperature is raised to 450°C in 2.2 hours, then raised to 900°C in 2.8 hours, kept warm for 30 minutes, then raised to 1200°C in 0.7 hours, kept warm for 30 minutes, and finally cooled naturally to room temperature to obtain a diatomite ceramic with a glaze layer thickness of 0.7 mm.

[0035] Example 3: A method for preparing diatomite ceramics

[0036] Preparation of modified diatomaceous earth: diatomaceous earth, cellulose phosphate and deionized water were mixed in a mass ratio of 5:1:40, ultrasonically stirred at a speed of 500 r / min for 40 minutes, filtered, dried and ground into fine powder to obtain modified diatomaceous earth.

[0037] Preparation of ceramic green body: firstly, 20 parts of the prepared modified diatoms are mixed with 70 parts of diatomite, 10 parts of kaolin, 10 parts of quartz, 5 parts of feldspar, 5 parts of flux (mixed by potassium oxide powder and sodium silicate in a mass ratio of 2:1), 5 parts of pore-forming agent (including graphite powder, silicon carbide and sodium carbonate in a mass ratio of 0.5:1:1), 8 parts of the first binder (including bentonite, sodium carboxymethyl cellulose and sodium silicate in a mass ratio of 1:1:2), 3 parts of reinforcing agent (including mullite fiber and alumina powder in a mass ratio of 1:1), and water is added in a ball mill for grinding, sieving and forming into a ceramic green body with a moisture content of 25%. The particle size of diatomite, modified diatomite, kaolin, quartz and feldspar is preferably 350 mesh. Then, after the ceramic body is dried, it is sintered. At room temperature, the temperature is uniformly increased to 300°C, fired for 3.5 hours, then uniformly increased to 950°C, fired for 6 hours, then uniformly increased to 1250°C, fired for 2.5 hours, and finally naturally cooled to room temperature to obtain a fired ceramic body. Preferably, when the ceramic body is dried and the difference in moisture content inside and outside the ceramic body is maintained at 1%, the ceramic body is sintered.

[0038] Preparation of ceramic glaze: 50 parts of the prepared modified diatomite are mixed with 10 parts of mica powder, 10 parts of talc powder, 5 parts of feldspar, 3 parts of zinc oxide, 3 parts of a second binder (including sodium silicate and sodium hexametaphosphate in a mass ratio of 1:1), 3 parts of a stabilizer (including zirconium silicate and magnesium oxide in a mass ratio of 1:1), 3 parts of a dispersant (including hydroxymethyl cellulose, sodium silicate, sodium humate and polyacrylamide in a mass ratio of 1:1:1:2), and 1 part of a wear-resistant additive (including wollastonite and calcium phosphate in a mass ratio of 1:0.8), and water is added to the ball mill for grinding and sieving to obtain a ceramic glaze with a moisture content of 55%. The particle size of the modified diatomite, mica powder, talc powder and feldspar is preferably 350 mesh.

[0039] Preparation of diatomite ceramics: first apply the obtained ceramic glaze to the fired ceramic body to form a glaze layer. Then, after the glaze layer on the ceramic body is dried, glaze firing is performed. At room temperature, the temperature is raised to 500°C in 2.5 hours, then raised to 950°C in 3 hours, kept warm for 30 minutes, then raised to 1250°C in 1.5 hours, kept warm for 30 minutes, and finally cooled naturally to room temperature to obtain a diatomite ceramic with a glaze layer thickness of 0.8 mm.

[0040] Embodiment 4:

[0041] This embodiment 4 refers to the method of embodiment 2, and the difference from embodiment 2 is that the reinforcing agent in the step of preparing the ceramic body is aluminum silicate fiber and silicon carbide powder in a mass ratio of 1:1. See Table 1.

[0042] Embodiment 5:

[0043] This Example 5 refers to the method of Example 2, and the difference from Example 2 is that the reinforcing agent in the step of preparing the ceramic body is basalt fiber and zirconium oxide powder in a mass ratio of 1:1. See Table 1.

[0044] Embodiment 6:

[0045] This Example 6 refers to the method of Example 2, and the difference from Example 2 is that in the step of preparing the ceramic body, the reinforcing agent is mullite fiber, aluminum silicate fiber, aluminum oxide powder and silicon carbide powder in a mass ratio of 0.5:0.5:0.5:0.5. See Table 1.

[0046] Embodiment 7:

[0047] This Example 7 refers to the method of Example 2, and the difference from Example 2 is that the reinforcing agent in the step of preparing the ceramic body is aluminum silicate fiber, basalt fiber, aluminum oxide powder and zirconium oxide powder in a mass ratio of 0.5:0.5:0.5:0.5. See Table 1.

[0048] Comparative Example 1:

[0049] This comparative example 1 refers to the preparation method of diatomite ceramics of example 2, and the difference from example 2 is that when preparing the ceramic body, 18 parts of modified diatom and 65 parts of diatomite are replaced by 83 parts of diatomite; when preparing the ceramic glaze, 45 parts of modified diatomite are replaced by 45 parts of diatomite. See Table 1.

[0050] Comparative Example 2:

[0051] This comparative example 2 refers to the preparation method of diatomite ceramics in example 2, and the difference from example 2 is that when preparing the ceramic body, the flux is 3 parts of potassium oxide powder or 3 parts of sodium silicate. See Table 1.

[0052] Comparative Example 3:

[0053] This comparative example 3 refers to the preparation method of diatomite ceramics in example 2, and the difference from example 2 is that when preparing the ceramic body, the first binder is 6 parts of bentonite or 6 parts of sodium carboxymethyl cellulose or 6 parts of sodium silicate. See Table 1.

[0054] Comparative Example 4:

[0055] This comparative example 5 refers to the preparation method of diatomite ceramics in example 2, and the difference from example 2 is that when preparing the ceramic body, the reinforcing agent is 2 parts of mullite fiber or 2 parts of aluminum silicate fiber or basalt fiber. See Table 1.

[0056] Comparative Example 5:

[0057] This comparative example 5 refers to the preparation method of diatomite ceramics in Example 2, and the difference from Example 2 is that when preparing the ceramic body, the reinforcing agent is 2 parts of alumina powder or 2 parts of silicon carbide powder or 2 parts of zirconium oxide powder. See Table 1.

[0058] Comparative Example 6:

[0059] This comparative example 6 refers to the preparation method of diatomite ceramics in example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the second binder is 2 parts of polyvinyl alcohol or 2 parts of bentonite. See Table 1.

[0060] Comparative Example 7:

[0061] This comparative example 7 refers to the preparation method of diatomite ceramics in example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the stabilizer is 2 parts of zirconium silicate or 2 parts of magnesium oxide. See Table 1.

[0062] Comparative Example 8:

[0063] This comparative example 8 refers to the preparation method of diatomite ceramics in Example 2, and the difference from Example 2 is that when preparing the ceramic glaze layer, the dispersant is 2 parts of hydroxymethyl cellulose or 2 parts of sodium silicate or 2 parts of sodium hexametaphosphate or 2 parts of polyacrylamide. See Table 1.

[0064] Comparative Example 9:

[0065] This comparative example 9 refers to the preparation method of diatomite ceramics in example 2, and the difference from example 2 is that when preparing the ceramic glaze layer, the wear-resistant additive is 2 parts of wollastonite or 2 parts of calcium phosphate. See Table 1.

[0066] Comparative Example 10:

[0067] The preparation method of the diatomite ceramics of this comparative example 10 refers to that of example 2, but differs from example 2 in that when preparing the ceramic body, the temperature is directly raised to 1150-1250° C. and fired for 10-12 hours.

[0068] Comparative Example 11:

[0069] The preparation method of the diatomite ceramics of this comparative example 11 refers to that of example 2, and the difference from example 2 is that when preparing the diatomite ceramics, the glaze firing is directly heated to 1150-1250°C and fired for 5-7h.

[0070] Table 1

[0071]

[0072]

[0073]

[0074]

[0075]

[0076]

[0077]

[0078] Example 8: Performance test experiment:

[0079] 1. Test the deformation and cracking of the fired ceramic body surface

[0080] The fired ceramic green bodies were prepared by the methods of Examples 1-7 and Comparative Examples 1-5, and the surface of the green bodies was observed for deformation and cracking. The results of each comparative example are the comprehensive results of multiple tests conducted under the conditions of temperature, time, etc. of Examples 1-7. The test results are shown in Table 2:

[0081] Table 2

[0082]

[0083]

[0084] Combining the data of Examples 1-7 and Comparative Examples 1-5 in Table 2 to observe whether the surface of the fired ceramic body is deformed and cracked, it can be seen that:

[0085] The surfaces of the ceramic bodies fired in Examples 1-7 of the present invention had no deformation or cracking; however, the surfaces of the ceramic bodies fired in Comparative Examples 1-5 were subjected to multiple tests and found to be deformed or cracked.

[0086] In Comparative Example 1, the modified diatomite of the present invention was not added, and the surface of the fired green body was deformed and slightly cracked. It can be seen that the modified diatomite added in the present invention helps to reduce the deformation and cracking of the green body during the firing process to a certain extent.

[0087] In Comparative Example 2, the flux is a single substance, and deformation and cracking occur on the surface of the fired green body. It can be seen that the flux compounded with potassium oxide powder and sodium silicate in the present invention helps to reduce the deformation and cracking of the green body to a certain extent.

[0088] In contrast to Example 3, the first binder used a single substance, and deformation and cracking occurred on the surface of the fired green body. It can be seen that the first binder compounded with bentonite, sodium carboxymethyl cellulose and sodium silicate in the present invention helps to reduce the deformation and cracking of the green body to a certain extent.

[0089] In contrast to the case where the reinforcing agent in Examples 4-5 is a single substance, deformation and cracking may occur on the surface of the fired green body. It can be seen that the reinforcing agent of the present invention, which is a composite of inorganic fiber and inorganic powder, helps to reduce the deformation and cracking of the green body to a certain extent.

[0090] 2. Test the deformation and cracking of the ceramic glaze surface

[0091] The diatomite ceramics made by glazing the ceramic bodies fired by the methods of Examples 1-7 and Comparative Examples 6-9 were observed to see whether the glaze surface was deformed and cracked. The results of each comparative example are the comprehensive results of multiple tests conducted under the conditions of temperature, time, etc. in reference to Examples 1-7. The test results are shown in Table 3:

[0092] Table 3

[0093] Is the glaze surface deformed? Is the glaze surface cracked? Example 1 none none Example 2 none none Example 3 none none Example 4 none none Example 5 none none Example 6 none none Example 7 none none Comparative Example 6 Deformation Slight cracking Comparative Example 7 Deformation Slight cracking Comparative Example 8 Deformation Slight cracking Comparative Example 9 Deformation Slight cracking

[0094] Combining the data of Examples 1-7 and Comparative Examples 6-9 in Table 3 to observe whether the surface of the fired ceramic glaze layer is deformed and cracked, it can be seen that:

[0095] The surfaces of the ceramic glaze layers fired in Examples 1-7 of the present invention had no deformation or cracking; however, the surfaces of the glaze layers of Comparative Examples 6-9 were subjected to multiple tests and deformation or cracking was found.

[0096] In Comparative Example 6, the second binder is a single substance, and the fired glaze layer surface will be deformed and cracked. It can be seen that the second binder compounded with polyvinyl alcohol and bentonite in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0097] In Comparative Example 7, the stabilizer is a single substance, and the fired glaze layer surface will be deformed and cracked. It can be seen that the stabilizer of zirconium silicate and magnesium oxide added in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0098] In contrast to Example 8, in which a single substance was used as the dispersant, deformation and cracking occurred on the surface of the fired glaze layer. It can be seen that the dispersant compounded with hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0099] In Comparative Example 9, the wear-resistant additive used a single substance, and the glaze layer surface was deformed and cracked. It can be seen that the wear-resistant additive compounded with wollastonite and calcium phosphate in the present invention helps to reduce the deformation and cracking of the glaze layer to a certain extent.

[0100] 3. Test on the effect of firing temperature on the surface of ceramic body and deformation and cracking of ceramic body

[0101] 3.1. Prepare fired ceramic green bodies by the methods of Examples 1-3 and Comparative Example 10, and observe whether the green body surface is deformed and cracked. The test results are shown in Table 4:

[0102] Table 4

[0103] Is the surface of the blank deformed? Is there any crack on the surface of the blank? Example 1 none none Example 2 none none Example 3 none none Comparative Example 10 Deformation There is cracking

[0104] Combining the data of Examples 1-3 and Comparative Example 10 in Table 4 to observe whether the surface of the fired ceramic body is deformed and cracked, it can be seen that:

[0105] The preparation methods of Examples 1-3 of the present invention control the temperature and time of the ceramic body bisque firing in three stages, and the fired body surface is free of deformation and cracking. However, the preparation method of Comparative Example 10 uses a direct heating method, and the fired body surface will be deformed and cracked.

[0106] 3.2. Diatomite ceramics were prepared by the methods of Examples 1-3 and Comparative Example 11, and the surface of the glaze layer was observed to see whether it was deformed or cracked. The test results are shown in Table 5:

[0107] Table 5

[0108] Is the glaze surface deformed? Is the glaze surface cracked? Example 1 none none Example 2 none none Example 3 none none Comparative Example 11 Deformation There is cracking

[0109] Combining the data of Examples 1-3 and Comparative Example 11 in Table 5 to observe whether the surface of the fired ceramic glaze layer is deformed and cracked, it can be seen that:

[0110] The preparation methods of Examples 1-3 of the present invention control the temperature and time of glaze firing in three stages after glazing the ceramic body, and the fired glaze layer has no deformation or cracking on the surface. However, the preparation method of Comparative Example 11 uses a direct heating method, and the fired glaze layer has deformation and cracking on the surface.

[0111] 4. Test on the density of diatomite ceramics

[0112] The fired ceramic bodies and the glaze layers of diatomite ceramics obtained after glazing were prepared by the methods of Examples 1-7 and Comparative Examples 2-9, and the densities of the bodies and the glaze layers were measured respectively. The test results are shown in Table 6:

[0113] Table 6

[0114]

[0115]

[0116] Combining the data of the green body density and glaze layer density of Examples 1-7 in Table 6, the green body density of Comparative Examples 2-5, and the glaze layer density of Comparative Examples 6-9, it can be seen that:

[0117] The green body density of the ceramic green bodies fired in Examples 1-7 of the present invention is significantly higher than that of Comparative Examples 1-5. Since the difference between Comparative Examples 2-5 and Examples 1-7 of the present invention is only that the corresponding flux, first binder, and reinforcing agent are respectively single substances, it can be seen that the compounded flux, first binder, and reinforcing agent added in the present invention help to increase the density of the green body to a certain extent.

[0118] The density of the glaze layer of the diatomite ceramic obtained after glazing the ceramic bodies fired in Examples 1-7 of the present invention is significantly higher than that of the glaze layer of Comparative Examples 6-9. Since the difference between Comparative Examples 6-9 and Examples 1-7 of the present invention is only that the corresponding second binder, stabilizer, and dispersant are respectively single substances, it can be seen that the compounded second binder, stabilizer, and dispersant added in the present invention help to increase the density of the glaze layer to a certain extent.

[0119] It can be seen that the diatomite ceramics obtained in Examples 1-7 of the present invention have higher density than the diatomite ceramics obtained in Comparative Examples 2-9.

[0120] 5. Performance analysis of the green body raw materials of the diatomite ceramics fired in the present invention

[0121] The ceramic body of the present invention is based on diatomaceous earth as the main raw material, and modified diatomaceous earth is added, wherein cellulose phosphate is used to react with hydroxyl groups on the surface of diatomaceous earth to form new chemical bonds, thereby changing the surface charge and hydrophilicity and hydrophobicity of the diatomaceous earth, increasing its specific surface area and adsorption capacity, and facilitating the absorption of moisture and melted kaolin, quartz, feldspar, etc. during the firing process, reducing the deformation and cracking of the body during the firing process, increasing the strength of the body, and improving the firing rate.

[0122] The flux in the green body of the present invention is a mixture of potassium oxide powder and sodium silicate. The flux of potassium oxide and sodium silicate can reduce the firing temperature of the green body, promote the melting of raw materials, and improve the density of the green body. Potassium oxide can promote the formation of a glass phase at high temperature and fill the gaps between crystal particles. Sodium silicate can refine the crystal particles, thereby improving the fineness and density of the green body and making the surface of the green body smoother and more beautiful.

[0123] The first binder in the green body of the present invention includes bentonite, sodium carboxymethyl cellulose and sodium silicate, which increases the bonding compatibility between diatomite, modified diatomite, kaolin, quartz and feldspar, improves the strength of the green body, and further reduces the breakage rate of the green body. Among them, bentonite has good adsorption. When sodium silicate and bentonite are mixed, the interlayer hydrated ions of bentonite are replaced, so that its adsorption is enhanced, and the bonding compatibility between the raw materials of the green body is increased under the synergistic effect of sodium carboxymethyl cellulose, and during the green body sintering process, it is helpful to uniformly discharge the water inside the green body, adjust the drying shrinkage and sintering shrinkage of the green body, and improve the compactness and crack resistance of the green body.

[0124] The reinforcing agent of the present invention prevents cracks and breakage of the green body during the firing process through the combination of inorganic fibers and inorganic powders, thereby improving the strength and toughness of the green body. Among them, the inorganic fibers include at least one of mullite fibers, aluminum silicate fibers, and basalt fibers, which improves the crack resistance of the green body during the firing process, increases the toughness of the green body, and further improves the strength of the green body. The inorganic powder includes at least one of aluminum oxide powder, silicon carbide powder, and zirconium oxide powder, which helps to improve the density of the ceramic during the sintering process, reduce the sintering temperature and time, and optimize the sintering atmosphere to avoid excessive crystal growth, maintain a good microstructure, and further improve the strength of the green body.

[0125] Therefore, the ceramic green body in the present invention uses diatomite as the main raw material, and by adding modified diatomite, the deformation and cracking of the green body during the firing process can be reduced, the strength of the green body can be increased, and the firing rate can be improved; by adding a compounded flux, a first binder and a reinforcing agent, the ceramic green body has good density, crack resistance and deformation resistance while improving the strength of the green body.

[0126] 6. Performance analysis of the glaze material of the diatomite ceramic of the present invention

[0127] The glaze layer of the present invention adopts modified diatomite, mica powder, talc powder, feldspar and zinc oxide as basic raw materials. The mica powder can form layers of microstructures in the ceramic. During the firing process, these layered structures can effectively prevent the ceramic from cracking during the firing process, thereby enhancing the strength and toughness of the glaze layer; the talc powder can improve the rheology of the glaze, so that the glaze is easier to apply evenly during glazing, improve the glazing effect, and increase the whiteness of the ceramic glaze, so that the ceramic products appear whiter and more translucent; the talc powder helps to control the shrinkage of the glaze surface during high-temperature firing, avoiding the glaze surface from cracking due to excessive shrinkage; its chemical stability enables it to remain stable in a high-temperature environment, and it will not easily react with other chemical substances, thereby ensuring the durability of the glaze; the feldspar can reduce the melting temperature of the glaze, so that the glaze reaches a molten state at a relatively low temperature, which helps to reduce energy consumption and production costs, and can also improve the sintering effect of the ceramic products; the zinc oxide has a fluxing effect, which can reduce the melting point of the glaze in the low-temperature frit glaze, promote the melting of the glaze, and thus improve the smoothness and color of the glaze surface.

[0128] The second binder in the glaze layer of the present invention includes polyvinyl alcohol and bentonite, wherein polyvinyl alcohol and bentonite can improve the adhesion and hardness of the glaze, and enhance the smoothness, wear resistance and crack resistance of the glaze surface. Bentonite plays the role of a binder and a suspending agent, so that the glaze maintains sufficient consistency and fluidity, avoids sedimentation, and increases the uniformity of the glaze layer.

[0129] The glaze layer of the present invention adopts a composite stabilizer of zirconium silicate and magnesium oxide. Zirconium silicate has good chemical stability, so it will not be affected by the ceramic firing atmosphere, ensuring the stability of the glaze and the quality of the finished ceramic product, and can significantly improve the ceramic body glaze bonding performance, improve the hardness of the ceramic glaze surface, and increase the overall strength of the ceramic. Zirconium silicate can also improve the whiteness and brightness of the glaze layer after glaze firing, and enhance the aesthetics and durability of the ceramic product; magnesium oxide can enhance the thermal stability of the glaze, and synergize with zirconium silicate to reduce the cracking and deformation of the glaze layer caused by temperature changes, thereby improving the crack resistance, deformation resistance and wear resistance of the ceramic product.

[0130] The glaze layer of the present invention adopts a dispersant compounded with hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide. Hydroxymethyl cellulose can significantly improve the fluidity of the glaze slurry, make the glaze layer more uniform and delicate, increase the uniformity of the glaze layer, and prevent problems such as cracking and deformation caused by water loss during the molding process, thereby improving the crack resistance and deformation resistance of the glaze surface; sodium silicate increases the negative charge on the surface of the particles to enhance the repulsive force between the particles, thereby achieving a stable dispersion effect, and synergistically improves the fluidity and stability of the glaze with hydroxymethyl cellulose; sodium hexametaphosphate can improve The adhesion and hardness of the glaze, synergistically with sodium silicate, make the glaze surface brighter and more uniform, and improve the gloss and wear resistance of the glaze; polyacrylamide can reduce the viscosity and surface tension of the glaze, increase the spreading speed of the glaze, ensure that the glaze is evenly coated on the surface of the ceramic product, increase the fluidity of the glaze, make the glaze smoother during the coating process, reduce production time and cost, and control the viscosity and wetting properties of the glaze to ensure the stability of the glaze during heating and cooling, reduce cracks and defects during the sintering process of the product, and thereby increase the overall crack resistance and deformation resistance of the ceramic.

[0131] Wollastonite and calcium phosphate are also added to the glaze layer of the present invention. Wollastonite can improve the fusibility and fluidity of the glaze, make the glaze adhere to the ceramic surface more evenly, improve the glossiness of the ceramic products, and can improve the hardness and wear resistance of the glaze. Calcium phosphate improves the optical properties and aesthetics of the glaze by changing the microstructure of the glaze, while also increasing the hardness and wear resistance of the glaze, and reducing defects such as bubbles, bursts and cracks on the glaze, thereby improving the quality of the glaze.

[0132] The glaze layer of the present invention uses modified diatomaceous earth, mica powder, talc powder, feldspar and zinc oxide as basic raw materials, so that the glaze layer has certain strength and toughness, and improves the smoothness and color of the glaze surface; by adding a compounded second binder, stabilizer, dispersant, and wear-resistant additive, the ceramic glaze layer also has good density, crack resistance and deformation resistance.

[0133] It should be noted that the above invention content and specific implementation methods are intended to demonstrate the practical application of the technical solution provided by the present invention and should not be interpreted as limiting the scope of protection of the present invention. Those skilled in the art can make various modifications, equivalent substitutions or improvements within the spirit and principles of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A diatomite ceramic with crack resistance and high density, characterized in that: The diatomite ceramic comprises a body and a glaze layer; The embryo body comprises the following raw materials in parts by weight: 60-70 parts of diatomite, 15-20 parts of modified diatomite, 5-10 parts of kaolin, 5-10 parts of quartz, 1-5 parts of feldspar, 1-5 parts of flux, 5-8 parts of first binder, and 1-3 parts of reinforcing agent; The glaze layer comprises the following raw materials in parts by weight: 40-50 parts of modified diatomite, 5-10 parts of mica powder, 5-10 parts of talc powder, 1-5 parts of feldspar, 1-3 parts of zinc oxide, 1-3 parts of a second binder, 1-3 parts of a stabilizer, 1-3 parts of a dispersant, and 0.5-1 parts of a wear-resistant additive.

2. The diatomite ceramic according to claim 1, characterized in that The diatomite ceramic comprises a body and a glaze layer; The embryo body comprises the following raw materials in parts by weight: 65 parts of diatomite, 18 parts of modified diatomite, 8 parts of kaolin, 7 parts of quartz, 3 parts of feldspar, 3 parts of flux, 6 parts of first binder, and 2 parts of reinforcing agent; The glaze layer comprises the following raw materials in parts by weight: 45 parts of modified diatomaceous earth, 8 parts of mica powder, 8 parts of talc powder, 3 parts of feldspar, 2 parts of zinc oxide, 2 parts of a second binder, 2 parts of a stabilizer, 2 parts of a dispersant, and 0.8 parts of a wear-resistant additive.

3. The diatomite ceramic according to claim 1 or 2, characterized in that: In the embryo, The flux comprises potassium oxide powder and sodium silicate; The first binder includes bentonite, sodium carboxymethyl cellulose and sodium silicate; The reinforcing agent comprises inorganic fiber and inorganic powder, wherein the inorganic fiber is selected from at least one of mullite fiber, aluminum silicate fiber and basalt fiber, and the inorganic powder is selected from at least one of aluminum oxide powder, silicon carbide powder and zirconium oxide powder; The average particle sizes of the flux, the first binder and the reinforcing agent are all 10-15 μm.

4. The diatomite ceramic according to claim 1 or 2, characterized in that: In the embryo, the particle sizes of the diatomite, modified diatomite, kaolin, quartz and feldspar are all 300-350 meshes.

5. The diatomite ceramic according to claim 1 or 2, characterized in that: In the glaze layer, The second binder includes polyvinyl alcohol and bentonite; The stabilizer includes zirconium silicate and magnesium oxide; The dispersant includes hydroxymethyl cellulose, sodium silicate, sodium hexametaphosphate and polyacrylamide; The wear-resistant additives include wollastonite and calcium phosphate; The average particle sizes of the second binder, stabilizer, dispersant and wear-resistant additive are all 10-15 μm.

6. The diatomite ceramic according to claim 1 or 2, characterized in that: In the glaze layer, the particle sizes of the modified diatomite, mica powder, talc powder and feldspar are all 300-350 meshes.

7. The diatomite ceramic according to claim 1 or 2, characterized in that: The modified diatomaceous earth is prepared by mixing diatomaceous earth, cellulose phosphate and deionized water in a mass ratio of 5:1:

40.

8. A method for preparing diatomite ceramics according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Step 1): diatomaceous earth, cellulose phosphate and deionized water are mixed in a mass ratio of 5:1:40, ultrasonically stirred at a speed of 400-500 r / min for 30-40 minutes, filtered, dried and ground into fine powder to obtain modified diatomaceous earth; Step 2): the modified diatomite obtained in step 1) is mixed with diatomite, kaolin, quartz, feldspar, flux, first binder and reinforcing agent according to the raw material ratio of the diatomite ceramic body as claimed in claim 1 or 2, and ground with water in a ball mill, sieved and formed into a ceramic body; Step 3): After drying the ceramic body obtained in step 2), sintering is performed, at room temperature, the temperature is uniformly increased to 200°C-300°C, fired for 3-3.5 hours, then uniformly increased to 850-950°C, fired for 5-6 hours, then uniformly increased to 1150-1250°C, fired for 2-2.5 hours, and finally naturally cooled to room temperature and fired into shape; Step 4): the modified diatomite obtained in step 1) is mixed with mica powder, talc, feldspar, zinc oxide, a second binder, a stabilizer, a dispersant, and a wear-resistant additive according to the raw material ratio of the diatomite ceramic glaze layer as claimed in claim 1 or 2, and ground and sieved in a ball mill to obtain a ceramic glaze; Step 5): applying the ceramic glaze obtained in step 4) to the ceramic body formed by firing in step 3) to form a glaze layer, and after the glaze layer on the ceramic body is dried, glaze firing is performed. At room temperature, the temperature is increased to 400°C-500°C in 2-2.5h, then increased to 850-950°C in 2.5-3h, and kept warm for 30min, and then increased to 1150-1250°C in 0.5-1.5h, and kept warm for 30min, and finally naturally cooled to room temperature to obtain diatomite ceramics with crack resistance and high density.

9. The preparation method according to claim 8, characterized in that: In step 2), the moisture content of the ceramic body is 20-25%; in step 4), the moisture content of the ceramic glaze is 45-55%.

10. The preparation method according to claim 8, characterized in that: The glaze layer thickness of the diatomite ceramic is 0.6-0.8 mm.

Citation Information

Cited By

  • Ceramic tile with granite texture and preparation method thereof

    CN120647333A